The Guidance program in the diocesan catholic schools system of the lice schools in the province of Laguna : an assessment - Logo, Adora S. (Manila : National University, 2005)
his study is significant as it assesses the guidance program in Liceo Schools in Laguna. It will be useful to the administrators, teachers, guidance counselors, parents, and students. The result of the investigation will help the guidance counselors discover the areas were students need more assistance, thereby provide adequate basis for preparing and determining appropriate guidance activities suitable to the needs of the students. Results of this study will help their guidance program more functional and more effective. Upon reading the results of this study, the researcher hopes that Guidance Counselor of every school not only in elementary, in high school but also to the collegiate level to re- evaluate and improve all the necessary innovations and revisions of their guidance programs.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.
Keywords: GUIDANCE PROGRAM